Immersogeometric thermal analysis of flows inside buildings with reconfigurable components - Xu, Fei; Wang, Chenglong; Hong, Kun; Liu, Yanfang (Journal of thermal analysis and calorimetry, 2021)
The design and operation of energy sustainable buildings rely on the comprehensive understanding of how ventilation flows are influenced by different configurations. In this work, we present an immersogeometric framework for the thermal analysis of turbulent flows inside or around geometrically complex designs for this purpose. The framework utilizes a variational multiscale method to model the incompressible turbulent flows. We propose a streamline/upwind Petrov–Galerkin formulation for the advection–diffusion equation of energy balance and augment it with a discontinuity-capturing operator. Boundary representations (B-rep) of reconfigurable component designs are immersed into the background non-boundary-fitted fluid mesh, circumventing the labor-intensive and time-consuming boundary-fitted mesh generation process. Thermofluid analysis inside several building configurations is performed. The results demonstrate the potential of our immersogeometric framework in supporting the further investigations of energy-efficient sustainable buildings.